Inovasi Pembelajaran: Mengintegrasikan Pengenalan Diri dan Nilai Pancasila Melalui "Ruang Validasi" pada Sekolah Dasar - Setyaningrum, Julia; NurRohmah, Annisa; Noviani, Alfina; Kuswantini, Alivia (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This systematic literature review aims to examine the existing literature on the effectiveness of the Teams Games Tournament (TGT) model and educational card games in enhancing Pancasila education, particularly concerning self-introduction and value internalization in elementary schools. The study employs a systematic literature review method, utilizing keywords such as "Teams Games Tournament," "Pancasila education," "card game," "elementary school," and "self-introduction." Data were retrieved from prominent databases including Google Scholar, ScienceDirect, and ERIC. Articles published between 2016 and 2025 were included to ensure recency. A total of 15 relevant articles were analyzed. The results indicate that the TGT model significantly boosts student motivation, social skills, and understanding of Pancasila philosophy, while educational card games effectively improve conceptual comprehension and learning interest. In conclusion, integrating TGT and card games supports holistic Pancasila education, promoting both cognitive and socio-emotional development in elementary students.Tinjauan literatur sistematis ini bertujuan untuk mengkaji literatur yang ada mengenai efektivitas model Teams Games Tournament (TGT) dan permainan kartu edukatif dalam meningkatkan pembelajaran Pendidikan Pancasila, khususnya terkait pengenalan diri dan internalisasi nilai di Sekolah Dasar. Penelitian ini menggunakan metode tinjauan literatur sistematis, dengan kata kunci "Teams Games Tournament," "Pendidikan Pancasila," "permainan kartu," "sekolah dasar," dan "pengenalan diri." Data diambil dari database terkemuka termasuk Google Scholar, ScienceDirect, dan ERIC. Artikel yang diterbitkan antara tahun 2016 dan 2025 dimasukkan untuk memastikan aktualitas. Sebanyak 15 artikel relevan telah dianalisis. Hasil penelitian menunjukkan bahwa model TGT secara signifikan meningkatkan motivasi siswa, keterampilan sosial, dan pemahaman filosofi Pancasila, sementara permainan kartu edukatif secara efektif meningkatkan pemahaman konseptual dan minat belajar. Sebagai simpulan, integrasi TGT dan permainan kartu mendukung Pendidikan Pancasila secara holistik, mendorong perkembangan kognitif dan sosial-emosional pada siswa sekolah dasar.